PELANGGENGAN DINASTI POLITIK ‘SAMAWI’ SEBUAH STUDI PERILAKU PEMILIH MODEL PSIKOLOGIS DALAM PILKADA BANTUL TAHUN 2010 - RESIANA DINA ANINDA, RESIANA DINA ANINDA (Politika: Jurnal Ilmu Politik, 2012)
Abstract The existence of the elections on the one side it can have a positive effect that is actualized political rights that we have the right to choose and choosen from. But term limits two periods leadership post local autonomy implies limited opportunities for regional heads occupy a strategic position in the region. Consequently born the phenomenon of political dynasties in which the former head of the region trying to put people around him to continue his rule. As well as the phenomenon of political dynasties in Bantul, Idham leadership was replaced by Sri Suryawidati is none other than his wife. Victory Sri Suryawidati not be separated from the influence of political power 'Samawi' where he used the name 'Idha Samawi' as a political tool in order to win votes. He obtained a landslide victory, with 67.77 percent of the vote won. Society tends to choose Idha Samawi on the basis of psychological voting behavior, where they will choose the candidate who has the proximity to a party and feel close to the characters or a specific figure, in this case is 'Samawi'. But further, the existence of political dynasties can hinder the democratic process because it is basically the power is controlled by one person. In addition, aspects of the capabilities and qualities to be a leader tends to ignored. Keyword: Political dynasty, psychological voting behavior, figure, capabilities and qualities